TT

Cho biểu thức A=  (-a-b+c) - (-a- b- c)

Rút gọn biểu thức

XO
12 tháng 9 2020 lúc 16:31

Ta có : A = -(a - b + c) - (-a - b - c)

= -a + b - c + a - b + c

= 0

Bình luận (0)
 Khách vãng lai đã xóa
.
12 tháng 9 2020 lúc 16:47

A = (-a - b + c) - (-a - b - c)

= -a - b + c + a + b + c

= (-a + a) + (-b + b) + (c + c)

= 2c

Vậy A = 2c.

Bình luận (0)
 Khách vãng lai đã xóa
TI
13 tháng 9 2020 lúc 22:34

A=  (-a-b+c) - (-a- b- c)

= -a-b+c+a- b- c

= (-a+a) + (-b+b) + (c+c) Đã đổi dấu 

= 2c

=> A = 2c

Bình luận (0)
 Khách vãng lai đã xóa
H24
14 tháng 9 2020 lúc 17:45

Ta có: A = (- a - b + c) - (- a - b - c)

<=> A = - a - b + c + a + b + c

<=> A = 2c

Vậy A = 2c

Linz

Bình luận (0)
 Khách vãng lai đã xóa
NN
4 tháng 2 2021 lúc 15:08

\(A=\left(-a-b+c\right)-\left(-a-b-c\right)\)

\(=-a-b+c+a+b+c=2c\)

Bình luận (0)
 Khách vãng lai đã xóa